Liver stiffness measurement predicts the difficulty of Kasai procedure in biliary atresia: a single center retrospective analysis of 199 patients - Qiulong Shen; Yajun Chen; Chunhui Peng; Wenbo Pang; Zengmeng Wang; Dongyang Wu; Kai Wang; Xinjie Huang (BMC, 2019)
Abstract Background Kasai procedure is the standard initial treatment of infants with biliary atresia. The key to perform a successful surgery is to accurately remove the fibrous portal plate near the liver hilum. Yet how to estimate surgical difficulty pre-operatively remains unclear. This study aims to design an algorithm that predicts the difficulty of Kasai procedure using liver stiffness measurement (LSM). Methods One hundred ninety-nine patients were included from April 2012 to December 2016. The patients were all surgically diagnosed with biliary atresia. Group A comprised of patients with porta hepatis retraction (the angle between the plane of the fibrous porta plate and the plane of the medial liver closest to the plate was equal to or smaller than 90°), group B comprised of patients without porta hepatis retraction (the angle between the plane of the fibrous porta plate and the plane of the medial liver closest to the plate was greater than 90°). Liver function measurements and LSM were measured for all patients within three days before surgery. Results Our study included 19 cases in group A (9 males, 10 females) and 180 cases in group B (87 males, 93 females). LSM had statistical differences between the two groups, 28.10(14.90) kPa VS 10.89(7.10) kPa, P = 0.000. There was a significant relationship between LSM and operative age, TBA, AST, GGT (P = 0.000, 0.003, 0.003, 0.012, correlation coefficient = 0.323, 0.213, 0.207, 0.179). The AUROC of LSM was 0.919. When the cutoff value was 15.15 kPa(OR = 3.989; P = 0.000), the sensitivity, specificity, PPV, NPV and diagnostic accuracy were 0.947, 0.750, 0.285, 0.992 and 0.768, respectively. When the value was 23.75 kPa(OR = 3.483; P = 0.000), the sensitivity, specificity, PPV, NPV and diagnostic accuracy were 0.631, 0.950, 0.571, 0.960 and 0.919, respectively. Conclusions LSM can be used to predict the difficulty in dissecting fibrous portal plate, and in turn, the difficulty of Kasai procedure. LSM > 23.75 kPa suggests a more complicated surgery.